Агробактеріальна трансформація томатів (Solanum lycopersicon) геном лактоферину людини - Танасієнко, І.В.; Бузіашвілі, Н.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2014)
Aims. Chemicals are classical agents for the control of plant diseases, however, the emergence of new resistant pathogens strains and their toxins as well as chemicals’ limited biological activity and negative long-term effects both on human health and the environment are the challenges for biotechnologists to develop an alternative approach of plant protection. Methods. Cell and tissue culture protocols were combined with Agrobacterium-mediated transformation to obtain modified tomato plants. Results. A range of explants, culture mediums, pre-cultivation time and their combination were established for the development of the effective tomato transformation protocol. Therefore, the regeneration of green shoots from the transformed explants under the selective pressure has been obtained. Conclusions. The effective protocol for transformation of commercial tomato cultivar “Many maker” was obtained.